2018
DOI: 10.1021/acsnano.8b05763
|View full text |Cite
|
Sign up to set email alerts
|

Highly Compressible Wood Sponges with a Spring-like Lamellar Structure as Effective and Reusable Oil Absorbents

Abstract: Aerogels derived from nanocellulose have emerged as attractive absorbents for cleaning up oil spills and organic pollutants due to their lightweight, exceptional absorption capacity, and sustainability. However, the majority of the nanocellulose aerogels based on the bottom-up fabrication process still lack sufficient mechanical robustness because of their disordered architecture with randomly assembled cellulose nanofibrils, which is an obstacle to their practical application as oil absorbents. Herein, we rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
317
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 548 publications
(323 citation statements)
references
References 42 publications
5
317
1
Order By: Relevance
“…Scale bar: 500 and 500 nm. b–d) Reproduced with permission . Copyright 2018, American Chemical Society.…”
Section: Applicationsmentioning
confidence: 99%
See 3 more Smart Citations
“…Scale bar: 500 and 500 nm. b–d) Reproduced with permission . Copyright 2018, American Chemical Society.…”
Section: Applicationsmentioning
confidence: 99%
“…Oil–water separators are generally porous meshes, foams and sponges made from a wide range of materials, including metal, polymers, ceramics, fabrics, cellulose‐based derivatives, particles, and novel nanomaterials . Recently, Wang et al reported a highly compressible wood sponge with spring‐like lamellar structure (Figure b–d), which was fabricated by sequential chemical treatment, freeze drying and chemical vapor deposition of natural balsa wood. After silylation treatment, the original amphiphilic wood sponge became hydrophobic, which ensured the selective absorption of oil.…”
Section: Applicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…had introduced biomaterials like barley straw, flax straw, wheat and oat straws for adsorption of oil showing oil sorption capacity less than 7 g/g. [24] Also there were reports about the use of lignin-cellulosic sponge material for the absorption of oil and organic solvents from water, but the synthesis of such lignin based materials requires multistep procedures and by the use of harsh chemicals like NaClO 2 , [25] silane, [25] fluorinating [26] agents etc. Hence the feasibility and sustainability of the process are missing.…”
Section: Introductionmentioning
confidence: 99%